FEASIBILITY EVALUATION STUDY OF VANAME SHRIMP (Litopenaeus vannamei) CULTIVATION BUSINESS WITH TWO TYPES OF CAPITAL IN THE BUMI DIPASENA FISHING AREA, RAWAJITU TIMUR DISTRICT - Lutfiani, Ulfah; Abidin, Zainal; Setyawan, Agus; Damai, A Aman; Riantini, Maya (Universitas Mataram, 2025)
The research aims to determine the evaluation of the financial feasibility and sensitivity of the vannamei shrimp cultivation business in the Dipasena Earth Farming Area, East Rawajitu District on two types of capital, namely independent and borrowed capital. The research was carried out in the Dipasena Earth Farming Area, East Rawajitu District in April – May 2024. The total cost of the vaname shrimp cultivation business was IDR 72,454,423 in independent capital and IDR 80,003,175 in borrowed capital with business profits of -Rp 9,915,373 in independent capital and - IDR 20,596,075 in borrowed capital for 3 harvest periods in one year. Based on the calculation results Net Present Value (NPV), B/C Rasio, R/C Rasio, Internal Rate of Return (IRR), and Payback Period (PP) in both types of capital, the business is included in the criteria of not being feasible. Sensitivity analysis shows that businesses with both types of capital are sensitive to changes in conditions, in this case an increase in operational costs of 2.75% and a decrease in production of 10%.